DNA damage in patients who underwent minimally invasive surgery under inhalation or intravenous anesthesia - Braz, Mariana Gobbo [UNESP] (2011)
Recent studies have demonstrated the genotoxicity of anesthetics in patients who have undergone surgery and in personnel who are occupationally exposed to anesthetics. However, these findings are controversial. Herein, we used the comet assay (single-cell gel electrophoresis) to investigate the genotoxic effects of two volatile compounds [isoflurane (ISF) and sevoflurane (SVF)] that are used in inhalation anesthesia, and of one intravenous (iv) anesthetic compound [propofol (PF)]. The groups consisted of 45 patients who underwent minimally invasive surgery that lasted at least 2 h. Patients were classified as physical status I using the criteria of the American Society of Anesthesiologists (ASA) and were randomly allocated to receive ISF. SVF or PF anesthesia. Venous blood samples were collected at three time points as follows: before the premedication and the induction of anesthesia (T(0)); 2 h after the beginning of anesthesia (T(1)); and on the day following surgery (T(2)). DNA damage (strand breaks and alkali-labile sites) was evaluated in peripheral blood lymphocytes. For each patient, one hundred nucleoids were analyzed per time point using a semi-automated image system. Patients did not differ with respect to their demographic characteristics, the duration of surgery, or the total doses of intraoperative drugs. The amount of DNA damage was not different among the three groups before anesthesia (T(0)). No statistically significant (p > 0.05) increase in DNA damage was detected during (T(1)) or after anesthesia (T(2)) using three different protocols (ISF, SVF or PF). In conclusion, general anesthesia with inhaled ISF and SVF or iv PF did not induce DNA strand breaks or alkali-labile sites in peripheral lymphocytes. Therefore, our results show that the genotoxic risk of these anesthetics, for healthy patients undergoing minimally invasive otorhinological surgery, is low or even absent. (C) 2011 Elsevier B.V. All rights reserved.